Pengaruh Model Pembelajaran Auditory Intelectually Repetition (AIR) Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas IX SMP Negeri 2 Sumbul Kabupaten Dairi Tahun Pembelajaran 2023/2024 - Tiorinta Venesia Natalia Siboro; Goklas J manalu; Raikhapoor Raikhapoor; Masniar Sitorus; Rida Gultom (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The study aims to determine the positive and significant influence of the use of the Auditory Intelectually Repetition (AIR) learning model on the motivation to learn Christian Religious Education and Ethics of grade IX students of SMP Negeri 2 Sumbul, Dairi Regency for the 2023/2024 Learning Year. The research hypothesis is that there is a positive and significant influence between the Auditory Intelectually Repetition (AIR) learning model on the motivation to learn Christian Religious Education and Ethics of grade IX students of SMP Negeri 2 Sumbul for the 2023/2024 Learning Year. The experimental research method designed by One Shot Case Study is research by giving treatment / treatment to groups or samples and then observing the results. Also use inferential descriptive quantitative methods. The population of all grade IX students of SMP Negeri 2 Sumbul for the 2023/2024 Learning Year who are Protestant Christians a total of 192 people. The sample was determined by purposive sampling technique, namely class IX-3 which amounted to 34 people. Research instruments in the form of closed questionnaires and observations. The results of data analysis were obtained: a) The value of rcalculate = 0.556 > rtabel = 0.339 and tcalculate = 3.784 > ttabel = 2.042 shows a positive and significant relationship. b) Regression equation . c) The determination test is known to have an effect of 30.91%. d) Test the hypothesis obtained Fcalculate = 14.014 > Ftable = 3.32 then H0 is rejected and Ha is accepted. The study concluded that there was a positive and significant influence between the Auditory Intelectually Repetition (AIR) learning model on the motivation to learn Christian Religious Education and Ethics of grade IX students of SMP Negeri 2 Sumbul Learning Year